2004
DOI: 10.1007/s00526-003-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ideal knots

Abstract: We present a characterization of ideal knots, i.e., of closed knotted curves of prescribed thickness with minimal length, where we use the notion of global curvature for the definition of thickness. We show with variational methods that for an ideal knot γ, the normal vector γ (s) at a curve point γ(s) is given by the integral over all vectors γ(τ )−γ(s) against a Radon measure, where |γ(τ ) − γ(s)|/2 realizes the given thickness. As geometric consequences we obtain in particular, that points without contact l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
(46 reference statements)
1
36
0
Order By: Relevance
“…But by (18), (23) The following two lemmas and the theorem that follows are essential in determining the structure of the right-hand side g and therefore of the measure f . The main argument is the following.…”
Section: Van Der Heijden Peletier and Planquémentioning
confidence: 99%
See 2 more Smart Citations
“…But by (18), (23) The following two lemmas and the theorem that follows are essential in determining the structure of the right-hand side g and therefore of the measure f . The main argument is the following.…”
Section: Van Der Heijden Peletier and Planquémentioning
confidence: 99%
“…If one of the ends of this interval equals 0 or T there is nothing to prove; we therefore assume that min{x 0 , T − x 1 − 1} ≥ d > 0. Now multiply (18) with the function…”
Section: Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, there has been a great deal of interest in exploring the geometry of tight knots; the definition of thickness has been refined and fully understood [10], it has been shown that C 1,1 minimizers exist in each knot type [5,8,9], some minimizing links have been found [5], and a theory of ropelength criticality has started to emerge [4,21]. The development of this theory has been fueled by a steady stream of numerical data on ropelength minimizers, from Pieranski's original SONO algorithm [15] and Rawdon's TOROS [16], to second-generation efforts such as Smutny and Maddocks' biarc computations [6,19] and the RIDGERUNNER project of Cantarella, Piatek, and Rawdon.…”
Section: Introductionmentioning
confidence: 99%
“…An exciting recent development in this field of mathematics has been the formulation of a kind of Euler-Lagrange equation describing length-critical knots in terms of the set of self-contacts of their tubes [7,16,38]. This theory has allowed us to make some conjectures about the tightening process, but these conjectures have * e-mail: cantarel@math.uga.edu, supported by NSF DMS #0204862 † e-mail: piatek@cs.washington.edu, supported by NSF DMS #0311010 ‡ e-mail: rawdon@mathcs.duq.edu, supported by NSF DMS #0311010 Figure 1: A tight 7.2 knot as computed using our method.…”
Section: Introductionmentioning
confidence: 99%